Efficiency of Scheduled Commercial Banks in India - An Analytical Study - Sundaram, N.; Geetha, S.; Kanjana, E. N. (Indian Journal of Finance, 2008)
The scheduled commercial banks are supposed to play an important role in achieving the objective of economic development by providing effective institutional credit support to various regions/sectors/sections. Banking has been viewed as a catalytic agent that must develop and support not only single element of the national economy but also provide an effective link between the productive, distributive and consumption side of it. Performance evaluation of an organization depends upon the type and the objectives lying behind it. Performance evaluation of commercial banks is going to be different from the commercial undertakings because banks, apart from qualifying economic efficiency criteria, also have to satisfy certain social obligations.